Supporting Visual Analytics in Decision Support System: A Systematic Mapping Study - Gonzales, Gustavo Romão; Horita, Flávio (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
Visual Analytics is an emergent research field, which uses the machinery power to process large data volumes, as well as human reasoning to discover new insights hidden in enterprise data. Decision Support Systems can be enhanced by these features and thus support better decision-making within organizations. However, there is not a clear understanding of ongoing works that investigate the interplay and commonalities of these two topics. In this context, this work reports the results of a systematic mapping study carried out to provide an overview of ongoing studies on the software architecture of the decision support system to support visual analytics features. Study findings clearly showed that even though visual analytics features might be incorporated on software architectures, there is still a need for further research clarifying means of modelling and representing these features on architectural styles.